Analysis and Design of Tag Antenna Based UHF RFID for Libraries - Xue Jian-bin; He Fengjie; Wang Dong (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
A kind of UHF RFID tag antenna for library management is designed. The series of design requirements are proposed through rich analytics. Refer to the management model of intelligent library based on UHF RFID. For the antenna, the size is , adopting T-shaped matching which good for adjusting of antenna impedance matching, the center frequency by simulations isunder application environment, Return Loss is less than in the frequency band of , the minimum value of return loss is . Simulation results show that the tag antenna has a good performance under application environment for library. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7135